2017
DOI: 10.21511/imfi.14(3).2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Inventory management, cost of capital and firm performance: evidence from manufacturing firms in Jordan

Abstract: Several studies have examined the relationship between inventory management and firm performance. However, most of these studies ignore the impact of inventory types on the relationship. Moreover, the relationship is influenced by some factors such as cost of capital which has not been considered. This study examines the moderating effect of cost of capital on the relationship between inventory types and firm performance. The data of 48 firms for the period 2010-2016 which formed 279 firm-year observations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…This finding is in line with the works of Ahmed (2016) who found out a positive effect between inventory management and profitability. Similar results were also found in Mulindabigwi and Mulyungi (2017) in Rwanda and Ashraf and Muhannad (2017) in Jordan. The findings of this research contradicts that of Bawa et al (2018) which discovered an insignificant negative effect between inventory conversion period and ROA and likewise findings of Otuya and Eginiwin (2017) in Nigeria and Nirujah (2015) in Sri Lanka.…”
Section: Discussion Of Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is in line with the works of Ahmed (2016) who found out a positive effect between inventory management and profitability. Similar results were also found in Mulindabigwi and Mulyungi (2017) in Rwanda and Ashraf and Muhannad (2017) in Jordan. The findings of this research contradicts that of Bawa et al (2018) which discovered an insignificant negative effect between inventory conversion period and ROA and likewise findings of Otuya and Eginiwin (2017) in Nigeria and Nirujah (2015) in Sri Lanka.…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…Using SPSS to analyse the data, the finding of the study revealed inventory management having a significant positive effect with financial performance. Results were also similar for Mulindabigwi and Mulyungi (2017) in Rwanda, Ashraf and Muhannad (2017) in Jordan and Ahmed (2016) in Nigeria.…”
Section: Literature Reviewsupporting
confidence: 57%
“…These classification criteria provide a different perspective to view inventory which can be valuable depending on the underlying goal of the organization, and a wide range of mechanisms can impact each one. Multiple classification systems have been studied and compared against the ABC system and found to be more effective; some of these alternatives are deemed more effective [9,[11][12][13]. However, little has been developed on inventory classification concerning environmental sustainability aspects.…”
Section: Inventory Managementmentioning
confidence: 99%
“…In a developing economy such as Jordan's, Alrjoub and Ahmad (2017) conducted research on the moderating impact of cost of capital on inventory types and firm value as a proxy for business performance. According to the study, the cost of capital influences the relationship between inventory management and company performance.…”
Section: Literature Reviewmentioning
confidence: 99%